Aquatic Emerging Contaminants and Their Ecotoxicological Consequences (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Considering the worldwide problem of aquatic pollution, we proposed this reprint, which presents a collection of articles on different aspects of environmental pollution, from monitoring to the evaluation of toxicity. In particular, the volume concerns the issues specifically related to emerging contaminants in aquatic environments, such as plastics and pharmaceuticals. However, to confer to this volume a more holistic view, some articles on priority pollutants, such as heavy metals and pesticides, are also reported.